Strategi Kepemimpinan Wali Nagari dalam Meningkatkan Kinerja Pegawai di Nagari Sitalang Kecamatan Ampek Nagari Kabupaten Agam - Islam, Aldiniatul; Lestari, Rika; Wahyuni, Sri; Sari, Suci Permata; Syamsir, Syamsir (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
Leadership strategy is how a leader improves the performance of their employees in line with organizational goals. Improving performance is inevitably linked to several factors that can hinder a person's leadership. However, with the right strategies from a leader, these obstacles can be prevented or resolved using methods employed by leaders to ensure their success in leading an organization. In a government organization, a leader's strategy can determine the performance of an employee, depending on how a leader directs their employees to work so that they can work well and in accordance with the leader's instructions.